ON SOME I-CONVERGENT SEQUENCE SPACES DEFINED BY A SEQUENCE OF MODULI - Khan, V.A.; Suantai, S.; Ebadullah, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this article we introduce the sequence spaces $c_0^I(F), c^I (F)$ and $\ell_∞(F)$ for the sequence of modulii $F = (f_k)$ and study some of the properties of these spaces. The results here in proved are analogus to those by Vakeel.A.Khan and Khalid Ebadullah (Theory and Applications of Mathematics and Computer Science,1(2)(2012)22-30.)